The Role of Human Resource Management in Improving the Quality of Education at Budi Utomo Vocational High School Sokaraja Banyumas - Hidayah, Sarofatul (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Human resource management has an important role in improving the quality of education, if the management of human resource management in a school is said to be good, the quality of the school will also be good. This study aims to determine the human resource management at SMK Budi utomo Sokaraja, how the quality of education at SMK Budi Utomo Sokaraja, whether the influence of human resource management on improving the quality of education at SMK Budi Utomo Sokaraja. The approach used in this research is a qualitative approach and case study design. Data collection techniques were obtained through interviews, observation and documentation. The data analysis used interactive analysis, namely data reduction, data presentation and data verification. Extension of participation and data triangulation were used to seek data validity. This research resulted in data that human resource planning at SMK Budi Utomo Sokaraja is structured based on activities from the analysis of causal factors, through annual evaluations. While the process of recruitment of teaching and education personnel is by analyzing position needs, planning the recruitment process, then placing job advertisements, conducting interviews and the last stage is selecting candidates needed by the institution. Human resource development at SMK Budi Utomo Sokaraja, especially for teaching staff, is by participating in training, training, workshops and subject teacher meetings (MGMP). As for the education staff, they are involved in training librarians, assets, correspondence and other trainings.